2022
DOI: 10.3390/cells11152435
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Transcriptomic Analysis of Arsenic-Induced Bladder Carcinogenesis

Abstract: Arsenic (sodium arsenite: NaAsO2) is a potent carcinogen and a known risk factor for the onset of bladder carcinogenesis. The molecular mechanisms that govern arsenic-induced bladder carcinogenesis remain unclear. We used a physiological concentration of NaAsO2 (250 nM: 33 µg/L) for the malignant transformation of normal bladder epithelial cells (TRT-HU1), exposed for over 12 months. The increased proliferation and colony-forming abilities of arsenic-exposed cells were seen after arsenic exposure from 4 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Finally, the enriched product was sequenced using the Illumina HiSeq 2,000/2,500 platform, and paired ends were generated. The raw data was analyzed and differential expression analysis was performed using the previously described method (Shukla et al, 2022).…”
Section: Rna Isolation Cdna Library Construction and Rna Sequencingmentioning
confidence: 99%
“…Finally, the enriched product was sequenced using the Illumina HiSeq 2,000/2,500 platform, and paired ends were generated. The raw data was analyzed and differential expression analysis was performed using the previously described method (Shukla et al, 2022).…”
Section: Rna Isolation Cdna Library Construction and Rna Sequencingmentioning
confidence: 99%
“…These findings could lead to more accurate descriptions of the role of As in molecular carcinogenesis. With respect to malignant cell transformation by As, Shukla et al [13] reported that stem cell activators may be crucial in enabling As-exposed cells to obtain a survival edge and reprogramming healthy epithelial cells into a cancer stem cell phenotype. Rehman et al [66] performed whole-genome gene-expression analysis in the blood of subjects exposed to arsenic (As) using microarrays.…”
Section: Metalsmentioning
confidence: 99%
“…RA then enters the nucleus and binds to retinoic acid receptors (RARs) or retinoid X receptors (RXRs) so as to induce the expression of its downstream target genes, which are especially focused on the cell differentiation and proliferation. 19 In the past studies, ALDH1A1 has been recognized as a diagnostic target in bladder cancer, 20 , 21 , 22 , 23 , 24 , 25 and ALDH1A1-induced drug resistance has been commonly reported in cancers. Moreover, specific ALDH1A1-targeted drugs developed by researchers have been used to treat cancers.…”
Section: Introductionmentioning
confidence: 99%